Analysis of GRDP Per Capita, Population Density and Foreign Investment against the Environmental Quality Index - Ar'rida, Maulidina; Sopiana, Yunita (PT. Riset Press International, 2023)
The aim of this research is to analyze the effect of GDP Capita, Population Density and Foreign Direct Investment on the Environmental Quality Index. This type of quantitative research with multiple linear regression model analysis. Using panel data in four provinces of Kalimantan Island in the 2010-2021 period. The results showed that population density has a significant effect on environmental quality. Meanwhile, GDP Per Capita and Foreign Direct Investment partially do not significantly affect environmental quality. The three independent variables simultaneously have a significant effect on the environmental quality index.